2020
DOI: 10.1186/s12886-020-01564-0
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the incidence of post-operative trichiasis in Africa

Abstract: Background Surgery for trichiasis is one of the pillars of the World Health Organization’s strategy for global elimination of trachoma as a public health problem. A high incidence of post-operative trichiasis or other poor surgical outcomes could jeopardize these efforts. In this review, we aimed to summarize the reported incidence of post-operative trichiasis and other poor outcomes of trichiasis surgery in Africa. Methods We conducted a systematic literature search using PubMed, Academic Search Premier, Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Second, there has been a high recurrence rate of trichiasis after surgical correction. 35 Third, even after no infections can be detected at the population level, inflammation in children’s conjunctivae may continue to occur. 36 Fourth, the relationship between environmental factors and trachoma are poorly understood and, in some areas, environmental corrections have failed to yield the expected impact.…”
Section: Introductionmentioning
confidence: 99%
“…Second, there has been a high recurrence rate of trichiasis after surgical correction. 35 Third, even after no infections can be detected at the population level, inflammation in children’s conjunctivae may continue to occur. 36 Fourth, the relationship between environmental factors and trachoma are poorly understood and, in some areas, environmental corrections have failed to yield the expected impact.…”
Section: Introductionmentioning
confidence: 99%
“…Trichiasis is an annoying, irritating condition that commonly develops as a result of the conjunctival cicatrizing disorder, posing a risk to the vision and integrity of the globe. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in Ethiopia studies showed that lower prevalence of postoperative trichiasis than other countries. For example, a study done in Amhara region, Ethiopia reported that postoperative trichiasis rate was 24.7% whereas another study in Ambasel district, South Wollo zone, Amhara region it was 23.8% in 2020 [ 23 , 24 ]. The possible explanation might be poor quality of service or it might be suggested by reinfection of patients because of lack knowledge and poor practice towards trachoma transmission and prevention measures.…”
Section: Discussionmentioning
confidence: 99%